PENGARUH MUSEUM EXPERIENCE TERHADAP KEPUTUSAN BERKUNJUNG (Survei Pada Wisatawan Nusantara Yang Berkunjung di Museum Kereta Api Ambarawa) - Melyanti, Elsa Dwi; Andari, Rini; Ridwanudin, Oce (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
Indonesia has a lot of economic potential, especially in tourism. Tourism has a definition as a people activity which travelling from one place to another, stay outside their ordinary environtment no more than one year to relax, leisure and another activity which not related to work. In order to run tourism activity properly, it require supporting facilities such as tourist attraction, hotels, restaurants, and travel agent. Semarang is the city with a high activity tourism activity, it seen from much variety of tourist attraction. And the most interesting tourist attraction in Semarang is museum. Museum Kereta Api Ambarawa is the most visited museum by the tourist, it has strategic location and has very complete and diverse museum collections. Museum Kereta Api Ambarawa implement museum experience strategy to increase tourists arrival. The purpose of this research was to look for the findings in museum experience implementation, decision to visit and the impact of museum experience to tourist decision. Object in this research is domestic tourists who visiting Museum Kereta Api Ambarawa. The type of research is descriptive and verification, and this research used explanatory survey method, with systematic random sampling technique, with the samples of 1000 respondents. Data analysis technique used multiple linear regression with SPSS 20 for windows software as a tools. Data collecting technique using interviews and surveys. The research findings that museum experience with Recreation (X1), Sociability (X2), Learning Experience (X3), Celebrate Experience (X4) dimention has an impact to tourist travelling decision which consisting of product selection, brand selection, distribution channel selection, visiting time decision, and payment method used.